17 TELKOM UNIVERSITY BANDUNG LECTURERS TO PURSUE DOCTORATE AT USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 – 17 lecturers from Telkom University (TU) in Bandung Indonesia will be pursuing their Doctor of Philosophy (Ph.D) studies at the Graduate School of Business, Universiti Sains Malaysia (GSB USM) resulting from the Memorandum of Agreement (MoA) signed in June this year.